Pengaruh Sektor Perbankan Syariah dan Pasar Modal Syariah terhadap Financial Deepening di Indonesia - Iir Tsamrotur Rofa; Maryam Batubara; Nurul Jannah (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2023)
The purpose of this research is to analyze aspects that influence financial deepening in Indonesia. The variables used in this study are ThirdParty Funds (DPK), Financing, Corporate Sukuk, State Sukuk for Financial Deepening in Indonesia. The analysis was carried out using monthly data published by Bank Indonesia and the Financial Services Authority in the study period from January 2018 to December 2022. The method of analysis in this study was to use multiple linear regression. The regression model obtained with a value of 0.005 shows that the variables of ThirdParty Funds (DPK), Islamic Financing, State Sukuk, Corporate Sukuk simultaneously have an influence on Financial Deepening in Indonesia. Partially, this study shows that the value of 0.261 ThirdParty Funds (DPK) is not significantly affected by Financial Deepening, as is the case with Financing with a value of 0.851 Financing is not affected by Financial Deepening. The results of this study explain that Corporate Sukuk with a value of 0.001 has a significant effect on Financial Deepening, as well as for State Sukuk with a value of 0.046, which segmentally has a significant influence on Financial Deepening in Indonesia. Future researchers are expected to be able to add other independent variables that can affect financial deepening, seeing that there are still more than 40% of factors that influence financial deepening that come from outside the variables studied.